The Capacity of Lower-Level Health Centres to Manage Noncommunicable Diseases in Uganda - Turyamureeba, Robert (East African Journal of Health and Science, 2025)
With funding from the Danish Civil Society Fund (CISU), and supported by the Danish NCD Alliance (DNCDA) and Uganda Non Communicable Diseases Alliance (UNDCA), the study focused on assessing the capacity of lower-level Health Centres (HC III & HC IV) to manage Non-Communicable Diseases (NCDs) in Uganda. Specifically, the survey assessed the capacity of HC III and HC IV units to: (i) detect the main NCDs (cancer, diabetes and heart disease); (ii) offer clinical care, including timely referral of patients with NCDs; and (iii) raise awareness, through health education and health promotion, on major risk factors to NCDs. The survey focused mainly on Cancer, Diabetes and Heart Diseases as the most prevalent NCDs. Using a cross-sectional survey design that embraced both qualitative and quantitative methods, the study found that HCs III and IV had inadequate technology, medicines, facilities, policies, record-keeping, human resource capacity to manage NCDs and conduct effective health education and promotion. As such, the study recommended that: the staffing norms of all levels of HCs should be upgraded; funding should be increased at the district level; the salaries and general working conditions of HC workers should be improved; and all HC health personnel should be trained in NCD management.